A Maltese adaptation of the Boston Naming Test: A shortened version. (1st November 2016) - Grima, Ritienne; Franklin, Sue
ABSTRACT: The Boston Naming Test (BNT) is the most widely used naming test worldwide in research and clinical settings. This study aimed to develop a method for adapting the BNT to suit different linguistic and cultural characteristics using the example of Maltese in a bilingual context. In addition, it investigated the effects in Malta of age and level of education on naming performance. The words of the BNT were first translated into Maltese. The test was then piloted to establish target and alternative responses. Naming performance data were later collected from individuals of different ages and levels of education. Only 38 BNT items had at least 70% name agreement. Main effects of age and education were found. A Maltese adaptation was proposed using 38 items and lenient scoring. Similar procedures may be used in other bilingual populations. The study suggests that normative data should be stratified according to age and education.